1975
DOI: 10.1177/030006057500300310
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mazindol (Teronac) with Diethylpropion in the Treatment of Exogenous Obesity

Abstract: Fifty obese patients were entered into a 12-week parallel group study of mazindol with diethylpropion in a general practice group. Both drugs produced weight loss, but patients on mazindol lost 19.9 lbs in 12 weeks, while those on diethylpropion lost 11.6 lbs, a statistically significant difference (p less than 0.01). At each visit during the trial, patients had lost more weight with mazindol, but this was only significant statistically in the period 8-12 weeks (p less than 0.01). Patients developed tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…In addition, HbA1c and blood pressure remained mostly unchanged in both treatment groups. Regarding the efficacy of mazindol on weight reduction, our results are in agreement with 2- to 16-week studies [ 19 , 20 , 21 , 22 ]. Unlike our trial, other studies also found improvements in insulin sensitivity and other glycemic parameters alongside BW reduction [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, HbA1c and blood pressure remained mostly unchanged in both treatment groups. Regarding the efficacy of mazindol on weight reduction, our results are in agreement with 2- to 16-week studies [ 19 , 20 , 21 , 22 ]. Unlike our trial, other studies also found improvements in insulin sensitivity and other glycemic parameters alongside BW reduction [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…Only mazindol and 11698 JL have been studied in humans and the anorectic activity demonstrated by these drugs in several selected clinical trials is summarized in Table IV. a. Mazindol. Mazindol (3 mg/day) was equivalent to phenmetrazine (75 mg/day) (Kornhaber, 1973), equal to (Kornhaber, 1973) or superior to (Defelice et al, 1973) amphetamine (15 mg/day), equal to fenfluramine (up to 160 mg/day) (Goldrick et al, 1974), and superior to diethylpropion (75 mg/ day) (Murphy et al, 1975) in achieving weight reduction. Mazindol (3 mg/day) was equivalent to phenmetrazine (75 mg/day) (Kornhaber, 1973), equal to (Kornhaber, 1973) or superior to (Defelice et al, 1973) amphetamine (15 mg/day), equal to fenfluramine (up to 160 mg/day) (Goldrick et al, 1974), and superior to diethylpropion (75 mg/ day) (Murphy et al, 1975) in achieving weight reduction.…”
Section: Nonphenethylamine Anorectic Agentsmentioning
confidence: 96%
“…A new non-amphetaminic tricyclic anorexiant (mazindol) has been found very effective, and to have a higher tolerance with an equal anorexiant effect than many drugs in commerce (De Felice, Chaykin & Cohen 1973, Conte 1973, Bradley, Blum & Shelb 1974, Murphy et al 1975, Enzi & Baritussio 1975, Evans & Wallace 1975.…”
Section: Introductionmentioning
confidence: 99%